2017
DOI: 10.1111/jcmm.13183
|View full text |Cite
|
Sign up to set email alerts
|

Roles ofST2,IL‐33 andBNPin predicting major adverse cardiovascular events in acute myocardial infarction after percutaneous coronary intervention

Abstract: This study investigated roles of serum ST2, IL‐33 and BNP in predicting major adverse cardiovascular events (MACEs) in acute myocardial infarction (AMI) after percutaneous coronary intervention (PCI). Blood samples were collected from the included AMI patients (n = 180) who underwent PCI. All patients were divided into the MACEs and MACEs‐free groups. Enzyme‐linked immunosorbent assay was performed to measure serum levels of ST2, IL‐33 and BNP. Severity of coronary artery lesion was evaluated by Gensini score.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 34 publications
0
28
0
6
Order By: Relevance
“…In acute MI cases treated with PCI, BNP was shown to predict one-year major adverse cardiac events (203). In summary, it is possible to say that high NP levels at admission or in-hospital denote poor short-and long-term prognosis in STE ACS cases treated with either thrombolytics or PCI.…”
Section: Bnp In the Assessment Of Risk And Prognosis In St-segment Elmentioning
confidence: 93%
See 1 more Smart Citation
“…In acute MI cases treated with PCI, BNP was shown to predict one-year major adverse cardiac events (203). In summary, it is possible to say that high NP levels at admission or in-hospital denote poor short-and long-term prognosis in STE ACS cases treated with either thrombolytics or PCI.…”
Section: Bnp In the Assessment Of Risk And Prognosis In St-segment Elmentioning
confidence: 93%
“…In acute MI cases treated with PCI, it was reported that a BNP value above 285.73 pg/mL predicted one-year major adverse cardiac events with 96% sensitivity and 77% specificity (203). Another study reported that the best threshold NT-proBNP value for predicting in-hospital mortality in STEMI cases treated with primary PCI was 2300 pg/mL (201).…”
Section: Is There a Cut-off Value That Can Be Helpful In Clinical Use?mentioning
confidence: 99%
“…Elevated ST2 concentration is a predictor of major adverse cardiac events in ACS patients [115]. e serum ST2 level positively correlates with IL-33 and BNP levels, and all of these biomarkers are independent predictors of major adverse cardiac events in AMI patients undergoing PCI [116]. e 2017 ACCF/AHA guidelines for the Management of Heart Failure have specified ST2 receptors and galectin-3 as prognostic biomarkers for the prediction of hospitalization and death and to provide additional prognostic value in patients with HF [117].…”
Section: Suppression Of Tumorigenicity 2 (St2)mentioning
confidence: 99%
“…levels are elevated early in NSTE-ACS and predict 1-year mortality [10]. Wang YP's research showed that serum levels of ST2, IL-33 and BNP were positively correlate with MACEs in patients with acute myocardial infarction (AMI) after percutaneous coronary intervention (PCI) [28]. However, there was no study to investigate the long-term value of ST2 in the prediction of MACEs or all cause death in patients with CAD in a large population.…”
Section: Prognosis Value Of St2 On Cardiovascular Diseasementioning
confidence: 99%